ANALYSIS OF INFLUENCES OF TEST ITEMS AND LEARNING STYLES ON PERFORMANCE OF ENGINEERING STUDENTS ON THE EXAM - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2011)
The goal of the study was three-fold: to investigate mechanical student behaviors (e. g., changing answers) while taking mixed text exams (having multiple-choice, fill in the blank etc. questions); to determine if specific behaviors are associated with performance on the exam; and to determine if there are linkages of learning style, as measured by Grasha's Learning Style Inventory (LSI), with test-taking activities. We have tested on midterm, final and quiz exam applications that have more than 20 questions having different styles. This new paradigm allows collection of detailed test taking behaviors that can be used to generate more suitable tests to assess the students. Test taking activities have been extracted from the exams of a core course (ME313 Manufacturing Processes I) on 2010-2011 Fall Semester given to mechanical engineering students. Student exam-taking activities have showed considerable variability. Correlation of test-taking behaviors with performance on the exam revealed that mixed test exams are more practical. There are also significant linkages of learning styles with exam-taking behaviors. In summary, the use of grades and Grasha's LSI has allowed a better understanding of the linkages of test-taking behaviors with academic performances and learning styles. Based on these findings, learning strategies might be designed to help students coping with courses that rely heavily on test exams for assessing student achievement.
Keywords: Learning Styles; Engineering Education; Test Items; PREFERENCES; UNIVERSITY